Determinants of Tax Haven Utilization: Evidence from Australian Firms - Taylor, Grantley; Richardson, G.; Taplin, Ross (Wiley-Blackwell Publishing Asia, 2014)
This paper examines the major determinants of tax haven utilization based on a sample of 200 publicly listed Australian firms, over the 2006–2010 period (1,000firm-years). Our regression results show that variables relating to transfer pricing, intangible assets, an interaction term between transfer pricing and intangible assets, withholding taxes, performance-based management remuneration and multinationality are positively associated with tax haven utilization. We also find that corporate governance structures are negatively associated with tax have nutilization. The magnitude and significance of the regression coefficients indicate that transfer pricing, withholding taxes, intangible assets, an interaction term between transfer pricing and intangible assets, corporate governance and multinationality are the most important drivers of tax haven utilization.